2013
DOI: 10.1055/s-0032-1328331
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Attributes of Desert and Steppic Plants: A Review

Abstract: l " desert plants l " steppic plants l " antidiabetic l " oxidative stress l " reactive oxygen species (ROS) l " hypoglycemic effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 67 publications
1
26
1
Order By: Relevance
“…This result is in agreement with previous investigations where animals suffering from insulin dependent diabetics (type 1) showed increased lipid peroxidation [21,33]. It was also reported that diabetic patients are more susceptible to membrane damage [32,34]. However, mixture of PUFAs from stem bark Alstonia boonei and antidiabetic drug (METAG) caused a significant reduction in MDA content of diabetic-induced rats.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with previous investigations where animals suffering from insulin dependent diabetics (type 1) showed increased lipid peroxidation [21,33]. It was also reported that diabetic patients are more susceptible to membrane damage [32,34]. However, mixture of PUFAs from stem bark Alstonia boonei and antidiabetic drug (METAG) caused a significant reduction in MDA content of diabetic-induced rats.…”
Section: Discussionsupporting
confidence: 92%
“…These irreversible oxidative modifications modulate redox-sensitive signaling pathways and lead to altered inflammation, endothelial dysfunction, impaired secretion of insulin, and impaired use of glucose in the peripheral tissues [6]. Many plant extracts are known to restore these parameters in streptozotocin (STZ)-induced diabetes rats, and have been found to delay diabetic complications as a result of their antioxidant potential [7]. However, currently available drugs for diabetes mellitus show many limitations, such as adverse effects, limited efficacy, and high rates of secondary failure [2].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the Indian subcontinent is a renowned to be one of the major biodiversity center with about 45,000 plant varieties. In India, about 15,000 medicinal floras have been noted, and up to 7,000-7,500 plants are used by communities for therapeutics of various kinds of ailments [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In similar kind of view, western Rajasthan (Part of the Thar desert) having peculiar kind of medicinal plants which are used by local people from long back based on conventional wisdom for therapeutics of diabetes and other diseases [5,12,13]. The local desert plants having a huge and unique number of secondary metabolites and phytocompounds through the specific stress conditions of desert.…”
Section: Introductionmentioning
confidence: 99%